Study on the correlation between pore morphology of porous calcium silicate and high-capacity formaldehyde adsorption. Issue 13 (7th June 2021) - Wang, Xiaoyan; Sun, Junmin; Zhang, Yongfeng; Zhang, Yinmin
ABSTRACT: A novel porous calcium silicate (PCS) material with unique pore structure prepared from coal fly ash (CFA) was reported. The microstructure was investigated through X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy, nuclear magnetic resonance cryoporometry, and Brunauer–Emmett–Teller method. Model describing the nanostructure of the prepared PCS was proposed in this work. Results show that the prepared PCS has open pores, a high specific surface area, and multi-peak pore size distributions (macro-, meso-, and micropores). The unique conical pore structure and interconnected micro-, meso-, and macropores are favourable to the reduction of the diffusion resistance of gas molecules. Benefiting from such a valuable structure, PCS exhibits excellent gas adsorption properties. Used in formaldehyde (HCHO) adsorption experiment, PCS shows excellent properties, including high storage capacity and endurance. The saturated adsorption capacity of the prepared PCS is 2.056 mg/g, which is enhanced by fourfold compared with that of active carbon commercially used for formaldehyde adsorption. This work provides a new, efficient, and rational way to utilize CFA. The prepared material can be used as an efficient and cost-effective adsorbent of HCHO under ambient conditions. Furthermore, the microstructure and the correlation between pore morphology and gas adsorption properties of the prepared PCS are revealed. GRAPHICAL ABSTRACT: UF0001